Aktivitas Pergaulan Melalui Media Sosial dan Dampaknya Terhadap Karakter Religius Anak Nelayan SDN 23 Toli-Toli Kecamatan Baolan Kabupaten Toli-Toli - Fauzan, Muh (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to determine the character of fishermen's children at SDN 23 Baolan Subdistrict, Toli-Toli Regency and the influence of social media activities on their character. This research is a field research with a qualitative approach. Data collection techniques were conducted through observation, interviews, and documentation. Data analysis was conducted using method triangulation technique. The research findings show that social media has a significant influence on children's character, particularly in terms of religiosity. Children tend to imitate behaviors they observe on social media, including the use of inappropriate language, delaying religious practices, and neglecting proper manners. Other character aspects such as hard work, discipline, and social care are also affected, with a tendency toward decreased responsibility and empathy due to uncontrolled exposure to online content. Although there is potential for positive impact, the negative effects of social media use are more dominant, mainly due to a lack of supervision and guidance from parents.